THE INTERRELATION OF SOCIO-DEMOGRAPHIC FACTORS AND TOURISM SPENDING ALLOCATIONS POST-COV-19 PANDEMIC IN GUNUNGKIDUL REGENCY - Robby Wijaya; Nova Nova; Wika Harisa Putri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The Covid-19 pandemic made the tourism sector suspended and must struggle to bounce back. Gunungkidul is one of the regencies in the Province of the Special Region of Yogyakarta, which is serious about developing its tourism potential. However, the pandemic had a very significant impact on this sector, so extraordinary efforts were needed to restore economic growth contributed by the tourism sector. This study tries to re-identify the socio-demographic factors that are the key to the revival of Gunungkidul tourism and are associated with the amount of tourism expenditure allocated after the Covid-19 pandemic. Using multiple linear regression analysis and involving 504 respondents, only age affected the allocation of tourist spending of the three socio-demographic variables. In contrast, the other two variables, gender and occupation, did not affect the allocation of tourist spending